Pengaruh Bimbingan Kelompok Teknik Brainstorming terhadap Komunikasi Interpersonal Siswa SMP - Reza Bayu Samudra; Meilla Dwi Nurmala; Lenny Wahyuningsih (Lembaga Yasin AlSys, 2026)
Interpersonal communication skills are an essential competency that needs to be developed among junior high school students, yet studies that specifically examine the effect of group counseling using the brainstorming technique remain limited. This study aimed to analyze the effect of group counseling with the brainstorming technique on students’ interpersonal communication skills. A quantitative approach was employed using a pre-experimental one-group pretest–posttest design with six ninth-grade students of SMP Negeri 18 Kota Serang in the 2025/2026 academic year selected through purposive sampling. Data were collected using an interpersonal communication skills questionnaire and analyzed using a paired-samples t-test. The results showed a mean interpersonal communication skills score of 62.8 with a t-test value of –20.180 and a significance value (p-value) < 0.05, so the alternative hypothesis (Hₐ) was accepted. These findings indicate a significant effect of group counseling using the brainstorming technique on students’ interpersonal communication skills. The study concludes that group counseling services with the brainstorming technique play an important role in improving the quality of students’ social interactions and their confidence in communicating in the school environment, and thus are recommended for guidance and counseling teachers as an alternative service for developing interpersonal communication skills.